MANAJEMEN PEMELIHARAAN GEDUNG E, G, K DAN V POLITEKNIK NEGERI PADANG - Yan Partawijaya (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2022)
Building maintenance is a very important to do after a building is completed or used. Maintenance makes of the building longer, safety, strength and appearance. Maintenance can reduce damage to the building, comfort and safety for all building users. Analysis of the maintenance management buildings E, G, K and V Politeknik Negeri Padang for 2023, maintenance schedule for buildings E, G, K and V Politeknik Negeri Padang for structural, architectural and utility components is divided daily, weekly, monthly and yearly intervals. Time periode, daily maintenance includes work on floors, walls, ceilings, doors, windows, frames, clean water installations, security installations, sanitary equipment and electrical installations. Maintenance periode of weekly and monthly intervals includes the work of structures, floors, walls, doors, frames, clean water installations and air conditioning installations. Annual periodic maintenance includes work on structures, walls, ceilings, doors, frames, air conditioning installations, fire protection installations and security installations. The maintenance cost of buildings E, G, K and V Politeknik Negeri Padang Rp. 810,834,743.17 with the cost of structural components of Rp. 84,443.56, architectural components of Rp. 651,660,899.61 and utility components of Rp. 159,089,400.00. Keywords: Buildings, Maintenance, Time periode, Cost